Land Use Planning, Land Development and Sustainable Management of Great Zimbabwe World Heritage Site, Masvingo Province, Zimbabwe - Ashley L. C. Maganzo; Marlvern Mabgwe (Springer, Cham, 2022)
Land-use planning is the key for sustainable cultural heritage management efforts in it there is need to balance land development and cultural heritage management. Data collected through field survey and documentation, interviews and questionnaires, a pattern has emerged illustrating that land around Great Zimbabwe World Heritage Site (GZ-WHS) is undergoing modern development to meet land-use demands of certain sectors such as in line with the education, communal farming, housing, tourism and retail business. However, given the sensitivity of Great Zimbabwe World Heritage Site, both as a national monument and a World heritage site, it is of national and global interest that its physical and intellectual integrity are protected without impeding the development of the local community. This paper advocates that by adopting a more integrated approach, in which multiple stakeholders take part and parcel of land-use planning around Great Zimbabwe World Heritage Site, the balance between land development and world heritage management is achieved sustainably.